Extraction of medicinal compounds from botanicals using bulk liquid membrane in rotating film contactor: Recovery of vinblastine from catharanthus roseus. - A. Al-Hemiri, Adil; A. M. Mohammed, Sawsan; B. Alsaadi, Raheeq (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
The interest of application of liquid membrane (pertraction) processes for recovery of medicinal compounds from dilute ammoniacal leach solutions is demonstrated. Selectivity of the liquid membrane ensures a preferential transport of the desired solute from the native extract into the strip solution, vinblastine was successfully extracted from basic media (pH 9.2) and stripped by acidic media of sulfuric acid (pH= 1.3) applying continuous pertraction in a rotating discs contactor and using n-decane as liquid membrane. Transport of vinblastine in three-liquid-phase system was studied and performed by means of a kinetic model involving two consecutive irreversible first-order reactions. The kinetic parameters (apparent rate constants of the vinblastine extraction and re-extraction reactions (K1, K2), the maximum fraction of the vinblastine in the liquid membrane (XS.Max) and the time when this maximum is reached (TMax)) were calculated. Solute transfer into the LM is mainly diffusion-controlled.